Predictors of Cardiometabolic Risk - Pedro Enrique Miguel Soca (Universidad de las Ciencias Médicas de Cienfuegos, 2015)
An interesting work accomplished in Cienfuegos by Cedeño Morales and collaborators demonstrates a significant correlation of the abdominal perimeter with the criteria of the metabolic syndrome like: Hypertension, Hypertriglyceridemia and Hyper-glycemia. In this comment he will discuss on the predictors of cardiometabolic risk, a theme studied not only in Cuba but also in other countries, submitted to debate, and also has many polemic and controversial aspects, that deserve a more deep analysis.